Process variables optimization for heat pump drying of roselle calyx by using response surface methodology - Norhaida Hanum Ahmad Tajudin; Wei, Lun Ang; Siti Masrinda Tasirin; Masli Irwan Roslia (Penerbit Universiti Kebangsaan Malaysia, 2021)
Heat pump drying technology has been recognized for its capability to conserve energy consumption and product quality in drying process. Understanding the influence of drying conditions on product quality and optimisation are necessary to cut down the drying cost. In this study, the drying of Roselle calyx using heat pump dryer was optimized using response surface method where Central Composite Design (CCD) was employed to investigate the effects of independent variables: drying temperature (40-60ᵒC) and sample mass (100-300 g), on the response variables (drying time, energy consumption and colour changes). The drying study aimed to achieve minimum drying time, energy consumption and total colour changes. It was discovered that temperature factor has dominant effect on drying time while sample mass on energy consumption and colour changes. The interplay between the variables was closely related to heat transfer and moisture evaporation rates of the sample. The optimum drying conditions as determined were at drying temperature of 60ᵒC and sample mass of 100 g. Under these conditions, the drying time, energy consumption, and colour difference were 332.3 min, 27.05 kWh, and 4.29 ΔE, respectively. The optimization model was well validated since the difference between the predicted and experimental results was below 3%.